2012
DOI: 10.3892/ijmm.2012.1189
|View full text |Cite
|
Sign up to set email alerts
|

A novel GATA5 loss-of-function mutation underlies lone atrial fibrillation

Abstract: Abstract. Atrial fibrillation (AF), the most common sustained cardiac arrhythmia, is associated with significantly increased morbidity and mortality. Cumulative evidence highlights the importance of genetic defects in the pathogenesis of AF. However, AF is of remarkable heterogeneity and the genetic determinants of AF in a vast majority of patients remain illusive. In this study, the coding exons and splice junctions of the GATA5 gene, which encodes a zinc-finger transcription factor essential for normal cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 62 publications
(76 reference statements)
2
30
1
Order By: Relevance
“…Similarly, congenital cardiovascular malformations were previously confirmed in AF patients carrying GATA4, GATA5 or GATA6 mutations (49)(50)(51)(52)(53)(54)(55)(56)(57). Markedly, a long list of mutations in these genes has been implicated in a wide variety of congenital cardiovascular anomalies (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, congenital cardiovascular malformations were previously confirmed in AF patients carrying GATA4, GATA5 or GATA6 mutations (49)(50)(51)(52)(53)(54)(55)(56)(57). Markedly, a long list of mutations in these genes has been implicated in a wide variety of congenital cardiovascular anomalies (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Discussionmentioning
confidence: 84%
“…Developmental biology studies substantiate the key role for several transcription factors, including NKX2.5, GATA4, GATA5 and GATA6, in the normal cardiovascular morphogenesis (46)(47)(48), and multiple mutations in GATA4, GATA5 and GATA6 have been causally associated with AF (49)(50)(51)(52)(53)(54)(55)(56)(57). NKX2.5 is a member of the NK2-family of transcription factors and its expression and functions overlap with those of the GATA family during cardiovascular development, particularly in synergistic regulation of target gene expressions cooperatively with GATA4 (58), which justifies NKX2.5 as a prime candidate gene for AF.…”
Section: Introductionmentioning
confidence: 93%
“…The primer pairs used to amplify the coding exons and exon-intron boundaries of the GATA5 gene were described in a previous study (46). Polymerase chain reaction (PCR) was carried out in Veriti Thermal Cycler (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Thus it is obvious that cardiogenesis is a complex and dynamic process, which requires the harmonious orchestration of cardiac cell commitment, differentiation, proliferation and migration, and both environmental and genetic risk factors may disrupt the finely regulated biological process, resulting in CHD (12)(13)(14). Mounting evidence has demonstrated that an evolutionarily conserved network of transcription factors connecting signaling pathways with genes related to muscle growth, patterning, and contractility, including the most extensively investigated GATA and NK families, are crucial in cardiovascular morphogenesis (15)(16)(17), and germline mutations in NKX2-5 (18-28), GATA4 (29-41), GATA5 (42)(43)(44)(45)(46), and GATA6 (47-55) have been associated with CHD. Nevertheless, the genetic basis underlying CHD remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiogenesis is a complex and dynamic biological process that requires the orchestration of cardiac cell commitment, differentiation, proliferation and migration, and both environmental and genetic risk factors may perturb this exquisite temporal and spatial cooperation, leading to a wide variety of CHD (15)(16)(17)(18)(19)(20)(21)(22). A growing body of evidence underscores the key role of cardiac transcription factors in Novel PITX2c loss-of-function mutations associated with complex congenital heart disease DONG WEI 1 , XIAO-HUI GONG 1 embryonic cardiovascular morphogenesis, and a long list of mutations in the genes coding for cardiac transcription factors, including the NK and GATA families, have been associated with CHD (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). However, CHD is a genetically heterogeneous disease and the genetic defects responsible for CHD in the majority of patients remain unknown.…”
Section: Introductionmentioning
confidence: 99%